2019
DOI: 10.1002/pchj.297
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter gene variants modulate acute stress‐induced hippocampus and dorsomedial prefrontal cortex activity during memory retrieval

Abstract: The short (s) allele of a polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) is related to reduced serotonin transporter efficiency and an increased vulnerability to stress and mental disorders. In the present study, we investigated how 5-HTTLPR impacts on memory retrieval under stress and related neural activity by reanalyzing a small genetic neuroimaging data set. Twenty-seven healthy male volunteers participated in both the Trier Social Stress Test (TSST) and a respective contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
(115 reference statements)
0
4
0
2
Order By: Relevance
“…5HTTLPR variant studies with biological and cognitive factors underlying depression, such as childhood trauma, attempted suicide, stress, and anxiety, have been reported in different populations, thus contributing to a better understanding of the disease. The S allele of 5HTTLPR increases the risk of depression only in stressed individuals [52,53]; therefore, it should not be widely generalizable, only observable in limited situations and modest sample size [52,54,55]. On the other hand, the L allele's increased transcriptional activity is considered protective against depression, yet it has been associated with suicide, nicotine dependence, and attention deficit hyperactivity disorder [54,55].…”
Section: Httlpr Variant and Mdd Risk Factorsmentioning
confidence: 99%
“…5HTTLPR variant studies with biological and cognitive factors underlying depression, such as childhood trauma, attempted suicide, stress, and anxiety, have been reported in different populations, thus contributing to a better understanding of the disease. The S allele of 5HTTLPR increases the risk of depression only in stressed individuals [52,53]; therefore, it should not be widely generalizable, only observable in limited situations and modest sample size [52,54,55]. On the other hand, the L allele's increased transcriptional activity is considered protective against depression, yet it has been associated with suicide, nicotine dependence, and attention deficit hyperactivity disorder [54,55].…”
Section: Httlpr Variant and Mdd Risk Factorsmentioning
confidence: 99%
“…However, other studies found no effect of 5-HTTLPR (Duman and Canli 2015 ; Wüst et al 2009 ) and one even found higher cortisol levels in L allele carriers (Mueller et al 2011 ). Li et al ( 2019 ) found no effect on cortisol, but nervous mood as well as brain activity during memory performance under stress. Despite the inconsistency of single studies, a meta-analysis concluded that 5-HTTLPR has a small but significant effect on cortisol response with S allele carriers showing increased reactivity (Miller et al 2013a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The study shows that the severity of a person's stress early in life predicts his/her cortisol response to stress in adulthood, which may contribute to the risk of certain stress‐related illnesses. Second, the study by Li, Tang, Gao, Thiel, and Wolf () on genes and neuroimaging is an important contribution. The authors used fMRI to measure the brain activities that different serotonin transporter gene (5‐HTTLPR) genotypes carry while performing an emotional face‐recognition task under the acute stress induced by the Trier Social Stress Test.…”
mentioning
confidence: 99%